2011
DOI: 10.1063/1.3653824
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected size effect in the thermopower of thin-film stripes

Abstract: For low-dimensional materials, size effect of a physical property is usually expected to occur when one (or more) of the dimension sizes decreases to that comparable to or smaller than one of the intrinsic characteristic lengths, e.g., the mean free path. We report here an unexpected size effect, that in centimeter-long stripes of 100-nm-thick metallic thin films, a reduction of the absolute value of thermopower occurs when the stripe width is in the order of 30-50 μm, which is 100–1000 times larger than the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 47 publications
3
41
0
Order By: Relevance
“…1,2 We agree with the authors that when the cold ends are close to the heating zone, the temperatures at the cold pads will increase, and this is an important issue to be taken into account in many applications.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…1,2 We agree with the authors that when the cold ends are close to the heating zone, the temperatures at the cold pads will increase, and this is an important issue to be taken into account in many applications.…”
supporting
confidence: 86%
“…In the Comment, 6 the authors present COMSOL simulations and argue that our observed phenomena in dual-beam thin film thermal sensors 1,2 are not due to a sizedependent Seebeck effect as we claimed, but rather wiresize-dependent heat transport that causes unequal heating at the bonding pads, leading to a temperature difference DTc ¼ Tc W À Tc N , where Tc W and Tc N are the increased temperatures at the wide (W) and narrow (N) beams. Consequently, the observed voltage output DV indeed corresponds to a thermoelectric effect of a parasitic thermocouple formed between the metal structure and the bonding pad, i.e., DV ¼ DS DTc, where DS is the difference in Seebeck coefficient of the sensor film to Al lead.…”
mentioning
confidence: 55%
“…The structure of the novel sensor is similar to a conventional bimetallic thermocouple, but the two beams of the sensor are of different widths and composed of the same Ni thin film (or W, Pd, or Pt thin films, as shown in the Supporting Information). Using the size effect of the Seebeck coefficient in metal strips with different widths,18 we show that these novel sensors have a sensitivity of ca. 1 μV K −1 .…”
mentioning
confidence: 99%
“…1 In contrast to charge transport, experimental studies of heat transport in mesoscopic structures are scarce, 2,3 though interesting new physics have been predicted. For example, electron-lattice relaxation processes can lead to a difference between phonon and electron temperatures at small length scales.…”
Section: Introductionmentioning
confidence: 99%